Analisis Strategi Sosial Media Marketing Kopi Kenangan melalui Instagram Feeds - Putra, Ida Bagus Ardhi; Darmawan, I Made Dwi Hita (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to analyze the social media marketing strategy implemented by Kopi Kenangan on the Instagram feed posts of @kopikenangan.id This research uses a qualitative descriptive method with a netnographic approach. Data sources were taken from 108 Instagram feed contents of @kopikenangan.id from November 2023 to February 2024. The data analysis techniques involve both qualitative and quantitative descriptive analysis. The research findings indicate that the type of content used in the Instagram feed is predominantly video content, compared to Single Image and Carousel posts. Kopi Kenangan employs a content marketing strategy that includes Awareness, Promotion, Collaboration, User Generated Content, and Product Information. This strategy aims to increase product sales as well as enhance awareness and interaction with followers on the Instagram account @kopikenangan.id. The social media marketing strategy implemented by Kopi Kenangan can serve as a reference for other businesses that wish to maximize Instagram as a communication and marketing platform to enhance awareness and engagement with consumers.